Steroid therapy in COVID-19 as a triggering factor for Strongyloides stercoralis hyperinfection - Norberg , Antonio Neres; Norberg , Paulo Roberto Blanco Moreira; Manhães, Fernanda Castro; Mangiavacchi, Bianca Magnelli; Faial, Lígia Cordeiro Matos; Filho, Renato Mataveli Ferreira; Borges, Thaís Rigueti Brasil; Colete, Claudia Caixeta Franco Andrade (Seven Editora, 2023)
Strongyloides stercoralis is a nematode with worldwide geographical distribution, most frequent in tropical areas, especially prevalent in areas with poor sanitary conditions. The disease caused by S. stercoralis is known as strongyloidiasis and parasitism is usually asymptomatic. Infection by this nematode may, however, present severe symptoms in hosts with immune system deficiencies. The aim of this research is to investigate, through a review of current scientific literature, the treatment of severe COVID-19 with immunosuppressants as a triggering factor for Strongyloides stercoralis hyperinfection. There are scarce records in the scientific literature on Strongyloides stercoralis hyperinfection consequent to treatment of COVID-19 with steroid drugs, mainly in endemic areas. We believe that this complication may be highly underestimated. The finding of eosinophilia in the blood count of patients after receiving immunosuppressive therapy during COVID-19 corticoid treatment is an important marker for the possibility of Strongyloides stercoralis hyperinfection and should prompt laboratory studies for nematode screening, mainly serology and PCR. DOI:https://doi.org/10.56238/innovhealthknow-037